1994
DOI: 10.1136/vr.134.14.348
|View full text |Cite
|
Sign up to set email alerts
|

Ovine lentivirus induced indurative lymphocytic mastitis and its effect on the growth of lambs

Abstract: The effect of the indurative lymphocytic mastitis caused by infection with maedi-visna virus was quantified by comparing the pre-weaning growth of lambs from infected and uninfected ewes under the same conditions. A total of 73 infected, but clinically healthy, ewes and 75 ewes from a maedi-visna virus-free source were purchased to form a new flock; they were all three years old. The ewes were mated and the flock was managed as a normal field flock. Serum samples were taken at regular intervals and tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 0 publications
2
17
1
4
Order By: Relevance
“…In the present study positive correlation were demonstrated between CMT and infection. This result is in agreement with Pekelder et al [19] who indicated that MVV infection increases SCC in sheep. It is reported that PCR has a sensitivity and specificity of 94.7 and 84.5 %, respectively, relative to the p28 ELISA [20].…”
Section: Discussionsupporting
confidence: 83%
“…In the present study positive correlation were demonstrated between CMT and infection. This result is in agreement with Pekelder et al [19] who indicated that MVV infection increases SCC in sheep. It is reported that PCR has a sensitivity and specificity of 94.7 and 84.5 %, respectively, relative to the p28 ELISA [20].…”
Section: Discussionsupporting
confidence: 83%
“…For an average weight of animals around 30 kg, the weight loss estimated in this study is a much smaller percentage (2% to 8%) of live weight than found for other sheep diseases (Kirkwood, 1980;Coop et al, 1985;Pekelder, 1994;Sargison et al, 1995;Mackay et al, 1998). The effect is similar to a 6.7% reduction in lamb output due to footrot in ewes estimated from results presented by Symons (1978) but much lower than the 30% found by Stewart et al (1984).…”
Section: Discussioncontrasting
confidence: 59%
“…For example, estimates of the reduction of live weight in lambs infected with internal parasites range from 6.2% to 23% (Coop et al, 1985;Mackay et al, 1998). Sheep scab leads to a 53% reduction in growth rate in lambs (Kirkwood, 1980) and a 10% loss in birth weight (Sargison et al, 1995), while losses in lamb weaning weight due to Maedi-Visna have been estimated at 12% for the most severe cases (Pekelder, 1994). Based on results of Symons (1978) and Stewart et al (1984) it can be estimated that ewes infected with footrot have a reduced lamb output of 18%.…”
Section: Introductionmentioning
confidence: 99%
“…This type of mastitis is clinically difficult to detect and mainly consists in a diffuse hardening of the mammary gland often observed after parturition [12,25,26]. The main clinical sign is the lack of milk production, which is normally detected by a deficient growth of the lamb [34]. In all the target organs, lesions appear to be the consequence of viral replication in tissue macrophages [35].…”
Section: Introductionmentioning
confidence: 99%